The influence of human resource management practices and career strategy on career satisfaction of insurance agents - Tan, Fee Yean; Yahya, Khulida Kirana (Universiti Malaysia Sarawak, 2013)
This paper examined individual perceptions of organizational human resource management(HRM) practices and career strategies that influence career satisfaction. This study also proposed that career strategy would mediate the relationship between HRM practices and career satisfaction. Data was gathered through questionnaires from insurance agents (n =531) located in the Northern States of Peninsular Malaysia.Hierarchical multiple regression analysis revealed that HRM practices (training and development, and compensation) and career strategy were positively correlated to career satisfaction.Results also provided partial support for the mediating role of career strategy on the relationship between HRM practices (training and development, and compensation) and career satisfaction. The findings of this study have the potential to provide ideas to the examined insurance companies in order for them to assert more efforts to improve the availability and effectiveness of their training and development programs, and design more attractive compensation packages for their employees.